Examining The Integration of Faith and Qur'an Curriculum in Kuttab Ibnu Abbas - Sudrajat, Sudrajat; Muthoifin, Muthoifin; Nurhayati, Sri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This research aimed to analyze the integration of the Iman and Qur'an curriculum at Kuttab. This study employed a case study method with a qualitative approach to explore the integration of Iman and Qur'an curriculum at Kuttab Ibnu Abbas. Data was collected through semi-structured interviews were conducted with key stakeholders, including school administrators, curriculum developers, teachers, students, and parents. The data collected through interviews, observations, and document analysis were subjected to thematic analysis.the research found that Qur'anic education at Kuttab Ibnu Abbas aims to instill Qur'anic values through a comprehensive curriculum that includes reading, writing, tajweed (correct pronunciation), tahfidz (memorization), and tadabbur (reflection) of the Qur'an. Several factors influence the success of this faith and Qur'an education, such as having well-prepared human resources, employing the right teaching methods, and ensuring the commitment of santri guardians (student caretakers). And the inhibiting factors were some students may lack proficiency in reading the Qur'an, have concentration issues in class, or lack parental cooperation in supporting learning at home.